Dry Landslide in Sarwodadi Village, Pejawaran Sub-Regency; An Untypical Landslide in Banjarnegara Regency, Central Java Province, Indonesia - Ahmad Rif'an Khoirul Lisan; Muhammad Gazali Rachman; Tiara Sarastika; Oki Kurniawan (School of Postgraduate Studies, Diponegoro Univer, 2025)
Banjarnegara is known as a regency highly susceptible to landslides, with over half of its territory classified as having a high to very high level of landslide hazard. Mass movements in Banjarnegara, particularly within the Merawu Sub-watershed, are predominantly categorized as slides. Rainfall stands out as the primary triggering factor for landslides in this region. This study aims to dissect the causes and mechanisms behind a unique landslide event that occurred in Sarwodadi Village, Pejawaran Sub-regency, Pejawaran Regency, Central Java Province, on July 6, 2022, around 10:30 PM. Unlike typical occurrences, this landslide was not propelled by precipitation, which is commonly the principal catalyst for landslides in Banjarnegara. Employing a three-stage methodology involving secondary data collection, field observation, and data analysis, we have identified two potential explanations for the landslide event: the loss of support from the stress barrier and mass sliding. Given that the area remains an active mining site with inherent dynamics, proactive measures are imperative to mitigate the risk of future landslides. This is essential for safeguarding the safety of local mining activities, which constitute the primary source of income for many households in Sarwodadi and its environment. A comprehensive mapping and assessment initiative targeting areas with geological characteristics akin to those in Sarwodadi should be undertaken across Banjarnegara. Such endeavors would not only diminish the occurrence of landslides but also enhance public awareness concerning atypical landslide occurrences.